Musculoskeletal disorders and their relationship with physical activities among office workers: a review - Shariat, Ardalan; Mohd Tamrin, Shamsul Bahri; Arumugam, Manohar; Danaee, Mahmoud; Ramasamy, Rajesh (Malaysian Public Health Physicians' Association, 2016)
Lower back, neck and shoulder pain are the most prevalent musculoskeletal problems affecting office workers worldwide, and they have both personal and socioeconomic consequences as well. Several hypotheses regarding the underlying mechanisms and the maintenance behind office work-related musculoskeletal disorders have been presented. There is some evidence, based on epidemiological studies as well as studies upon smaller groups of subjects, that individuals who sit and work for a long time not only show cognitive impairment at the workplace, but also suffer from poorer and fragmented daytime sleep, in addition to increased risks of developing various psychological, physiological and medical impairments and musculoskeletal disorders. The related physical mechanisms behind musculoskeletal disorders are discussed in the context of new findings. The main causes, as well as varying levels in severity of musculoskeletal disorders, not to mention the link between such disorders in the neck, shoulder and lower back regions and physical activity among office workers are also stated. The main objective of this review paper is to conduct a systematic review to identify musculoskeletal disorders and how these disorders are correlated with physical activity among office workers. The results of this review indicate that the musculoskeletal disorder is a critical issue among office workers and the main cause is related to the absence of physical activity as well as the subjects’ sedentary lifestyle. As a practical message, regular physical activity can be effective in the prevention and decrease of physical discomfort among office workers who suffer from musculoskeletal pain.